Exotic plant invasions under enhanced rainfall are constrained by soil nutrients and competition. Issue 3 (1st March 2014) - Eskelinen, Anu; Harrison, Susan
Abstract : To predict the net impact of climate change on invasions, it is critical to understand how its effects interact with environmental and biotic context. In a factorial field experiment, we examined how increased late‐season rainfall influences the growth and reproductive success of two widespread invasive species ( Centaurea solstitialis and Aegilops triuncialis ) in heterogeneous Californian grasslands, and, in particular, how its impact depends on habitat type, nutrient addition, and competition with resident species. Rainfall enhancement alone exhibited only weak effects, especially in naturally infertile and relatively uninvaded grasslands. In contrast, watering and fertilization together exhibited highly synergistic effects on both invasive species. However, the benefits of the combined treatment were greatly reduced or offset by the presence of surrounding competitors. Our results highlight the roles of nutrient limitation and biotic resistance by resident competitors in constraining the responses of invasive species to changes in rainfall. In systems with strong environmental control by precipitation, enhanced rainfall may promote invasions mainly under nutrient‐rich and disturbed conditions, while having lesser effects on nutrient‐poor, native "refuges."